INDICATORS OF FLOOR SLABS REINFORCEMENT TECHNICAL AND ECONOMIC INVESTIGATION BY DIFFERENT TECHNOLOGIES - Molodid, O. S. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The paper presents the results of technical and economic indicators study of reinforcing monolithic reinforced concrete slab various methods, namely: the supply of metal beams with the installation of additional supports, external reinforcement of stretched zones using MAPEI technology, adhesion of metal plates and carbon fiber to the developed technology. There is established that the highest indicators of the materials cost, labor intensity and wages for the execution of works relate to the option of reinforcing the floor slab by supplying metal structures, and the lowest indicators have options for reinforcing the floor slabs using MAPEI technology and bonding carbon fiber under the developed technology. The cost of materials for reinforcing the plate in the developed technology with the adhesion of steel plates is the lowest, but complexity, wages and the duration of the work on this technology are much higher than other studied technologies of external reinforcement.
Keywords: reinforcement of floor slab; external reinforcement; carbon fiber; , technical and economic indicators.